INTEGRATING LOCAL WISDOM OF RIAU MALAY CULTURE IN ENGLISH LEARNING IN 4.0 ERA - Liya Astarilla Dede Warman; Hadriana; Elmustian Rahman (ELP (Journal of English Language Pedagogy), 2025)
Providing English materials based on local wisdom of Riau Malay is appropriate to improve the students’ English skill and also their cultural values and norms. Integrating moral values or local wisdom into English teaching and learning process can protect future generations from the deterioration of their national identity. The objectives of this research were to analyse the integration of local wisdom of Riau Malay Culture in English learning and the effects of the integration of local wisdom on students’ English skills. Systematic literature review was employed in the study by implementing PRISMA. This study utilized article databases and search engines namely Scopus, Semantic Scholar and Google Scholar to obtain the data. There were 11 articles as the data source which analyzed by employing narrative synthesis. The results of this study found that local wisdom of Riau Malay can be integrated into English learning namely reading, writing and speaking skills. Integrating Riau Malay Cultural values in English learning can enhance the students’ English ability and their cultural awareness in preserving local culture and national identity. Nevertheless, the studies related to the integration of local wisdom of Riau Malay Culture into English learning is very limited, this research is necessary to fill that gap.  It is also suggested for the next researchers to conduct further investigations related to this topic.